ANALISIS FAKTOR PRODUKSI DAN KEBUTUHAN TENAGA KERJA (LUAR KELUARGA) PADA USAHATANI PADI SAWAH DI KABUPATEN LEBONG PROVINSI BENGKULU - Evi Andriani (UNIVED Press, Universitas Dehasen Bengkulu, 2016)
This research purpose to know number of labor demand in demand of labor derived outside of household in paddy farming and find out the characteristics and factors which are influencing labour demand in paddy farming in Lebong District. The research was uses simple random sampling technique. The number of sampel are 30 farmer. The result of the research showed (1) that farmer 22,18 Day work Equvalent Mean/ farm for the labor of inside household, 1s 99,34 DWEM/farm for labor of outside household, and (2).The significant variabel in faktor of derived outside household that farm is field, wage, untilizing tractor in paddy farming.while price of fertilizer, price of pestised,price of product, is not significant to demand of labour derived in paddy farming. Key word: demand of labour derived outside of household, paddy farming